Hubungan Antara Penggenangan Dini dan Potensi Redoks, Produksi Etilen dan Pengaruhnya terhadap Pertumbuhan dan Hasil Padi (Oryza sativa) Sistem Tabela - IGK. Dana Arsana; Sudirman Yahya; A. P. Lontoh; H. Pane (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2003)
The research was conducted at the Rice Research Center, Sukamandi and at the Biotechnology Research Center,Bogor.  A two factors factorial experiment was arranged on Split Plot Design, where three levels of submerging: saturated, 5 and 10 cm in depth were assigned as the main plot and three lowland rice genotypes: IR 64, S. 3254-29-21-2 and S. 3382-2d-16-3 lines as subplots. The results indicate that submerging revealed a significant effect on  increasing the redox potential, pH, ethylene production, and yield,  however decreasing weed infestation. Almost there was no significant difference among three genotypes on their ethylene, growth and yield, and also on their responses to  the submerging treatment. Furthermore, submerging at 5 cm depth increased yield by 110 kg ha-I, or about 1.5 percent compared to just saturated condition. On the other hands, submerging at 10 cm depth increased yield by 612 kg-I. In  term of varieties, the promising lines of S,3254-29-21-2 and S.3382-2d-16-3 did not prove to have a difference with ' IR 64, in terms of their tolerance to early submerging condition. , " Key words: Submnerging, Redox potential, Ethylene, Direct sfeeding system